The influence of stage of pregnancy on digestion characteristics in beef cows - Beharka, A.; Cochran, B.; Harmon, D.; Avery, T. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Feed intake during the final trimester of gestation did not appear to vary significantly until 2 weeks before calving, after which it decreased dramatically. Measurements during two periods in the final trimester suggested that passage rate increased and digestibility decreased, as pregnancy proceeded.
Keywords: Beef; Pregnancy; Digestion; Feed intake